World economy and markets conjuncture - Kukharyk, Viktoriia V. (Lesya Ukrainka Volyn National University, 2021)
The normative academic subject is designed to acquaint students with the structure and features of the modern world economy and the economy of the regions, the current state, trends and prospects of the world market. The main purpose of the academic subject "World economy and markets conjuncture" is the formation of a system of theoretical knowledge in the analysis of socio-economic systems and models of the world development, of the main sections of markets, their functioning, expansion or contraction, the analysis of prices, supply and demand changes, mastering theoretical knowledge and practical skills in analyzing trends and processes occurring during the economic development of the world, identifying relationships and assessing the impact on regions integration into the modern world economy, identifying the peculiarities of individual national economies and their role in world economic relations.
Keywords: World economy; markets conjuncture